StTCP15 regulates potato tuber sprouting by modulating the dynamic balance between abscisic acid and gibberellic acid - Wang, Kaitong; Zhang, Ning; Fu, Xue; Zhang, Huanhuan; Liu, Shengyan; Pu, Xue; Wang, Xiao; Si, Huaijun (Frontiers in Plant Science, 2022)
The major stages of the potato life cycle are tuber dormancy and sprouting, however, there is still known very little of the mechanisms that control these processes. TCP (Theosinte branch I, Cycloidea, proliferationcell factors 1 and 2) transcription factors play a key role in plant growth and dormancy related developmental processes. Previous researches demonstrated that TCP transcription factor StTCP15 had a function in the promotion of dormancy. To elucidate the function of StTCP15 gene, it was cloned from potato cultivar “Desiree”, which encodes a polypeptide consisting of 414 amino acids and is mainly found in the nucleus. The potato tubers of StTCP15 overexpression lines sprouted in advance, while the potato tubers of StTCP15 down-regulated expression lines showed delayed sprouting. In addition, it was also found that overexpression lines of StTCP15 extremely significantly reduced the ratio of ABA/GA3, while the superoxide dismutase activity decreased, and the activity of peroxidase and catalase increased compared with the wild type. The opposite result was found in the down-regulated expression lines of StTCP15 gene. Three interacting proteins, StSnRK1, StF-Box and StGID1, were screened by Yeast two-hybrid, and verified by Bimolecular Fluorescence Complementation and Split-luciferase, indicating that StTCP15 could affect ABA and GA3 signaling pathways to regulate potato tuber dormancy and sprouting. Together, these results demonstrated that StTCP15 regulated potato tuber dormancy and sprouting by affecting the dynamic balance between ABA and GA3. The result could provide some information on the molecular mechanism of StTCP15 regulating potato tuber dormancy and sprouting.